Salmonella osteomyelitis due to Irak-4 deficiency - Türkyılmaz Uçar, Özge; Naiboğlu, Sezin; Kaplan Sarıkavak, Sibel; Ulaş, Selami; Turan, Işılay; Ayaz, Akif; Al, Serdar; Gökmirza Özdemir, Pınar; Çeliksoy, Mehmet Halil; Aydoğmuş, Çiğdem (My University, 2024)
[Abstract Not Available]
Keywords: IRAK-4; AML; Childhood